'My body's falling apart.' Understanding the experiences of patients with advanced multimorbidity to improve care: serial interviews with patients and carers. Issue 1 (28th May 2014) - Mason, Bruce; Nanton, Veronica; Epiphaniou, Eleni; Murray, Scott A; Donaldson, Anne; Shipman, Cathy; Daveson, Barbara A; Harding, Richard; Higginson, Irene J; Munday, Dan; Barclay, Stephen; Dale, Jeremy; et al.
Abstract : Objective: Multimorbidity is increasingly common in the last year of life, and associated with frequent hospital admissions. The epidemiology is well described, but patient perspectives are less understood. We report the experiences and perceptions of people with advanced multimorbidity to inform improvements in palliative and end-of-life care. Design: Multicentre study including serial, multiperspective interviews with patients and their family carers; an interpretive analysis of experiences and understanding of living with advanced multimorbidity. Participants: We recruited patients and their family carers using established UK clinical guidance for the identification of people anticipated to be in their last year of life. Settings: An acute admissions unit in a Scottish regional hospital; a large English general practice; a London respiratory outpatient clinic. Results: We analysed 87 interviews with 37 patients and 17 carers. They struggled with multiple changing medications, multiple services better aligned with single conditions such as cancer, and a lack of coordination and continuity of care. Family carers spoke of physical, mental and emotional exhaustion and feeling undervalued by professionals. Patients and carers frequently saw deteriorating health as part of 'growing old'. Many used a 'day-to-day' approach to self-management that hindered engagement with advance care planning and open discussions about future care. 'Palliative care' and 'dying soon' were closely related concepts for many patients, carers and professionals, so rarely discussed. Conclusions: Patients with advanced multimorbidity received less care than their illness burden would appear to merit. Some people did restrict their interactions with care providers to preserve autonomy, but many had a limited understanding of their multiple conditions, medications and available services, and found accessing support impersonal and challenging. Greater awareness of the needs associated with advanced multimorbidity and the coping strategies adopted by these patients and carers is necessary, together with more straightforward access to appropriate care.